Energy management system and supervision in a micro-grid using artificial neural network technique - Ezzitouni Jarmouni; Ahmed Mouhsen; Mohammed Lamhammedi; Hicham Ouldzira (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Nowadays, the combination of conventional and renewable energy sources such as solar energy is one of the most widespread solutions to surmount the challenge of the climate and energy crisis. In the presence of random behavior of photovoltaic systems and variable power demand by consumers, energy management is a real challenge. In this paper, we propose a new energy management technique based on artificial neural networks in a smart grid. This will ensure the continuous supply of electricity to the consumer in the presence of random operation in energy consumption and generation. The global system is modeled and simulated under the MATLAB/Simulink tool.